1)
2(a+b)
3(x-y)
3(3x+y)
5(2a-3b)
x^2(x-1)
x(2x^2 -3)
xy(1+x^2)
3x^2(3y-4)
xy(4yz-3)
radical(3)abc(3a+2c)
5radical(3)ab(4a^2b-radical(2))
2)
3(a+b-c)
x(x^3+2x^2-1)
xy(1-2x-y)
3(y^2-2y^3+3)
a^2(ab^2-2-b^2)
x(9x^3-12x+8)
6a^2b^2(4a-2b-1)
xy(2-3x-6y)
x(x^3-x^2+2x-3)
xy(1+x+y-xy)
a(a^4-3a^3+2a-1)
xyz(x^2-2y+3xy^2z^3-1)
m)radical(2)xy(radical(6)xy-radical(3)y+
radical(3)x+2-radical(6)x^2y^2)
3)
a)(x+1)(y+z)
b)(y-1)(x-2)
c)(2y+1)(x^2-3)
d)(x+3)(x+2-x)=2(x+3)
e)(2x-1)(2x-1+3)=(2x-1)(2x+2)=
=2(2x-1)(x+1)
f)(x+5)(x+5-x)=5(x+5)
g)(y-1)(y-1+x+2)=(y-1)(x+y+1)
h)(x+3)(x+1+x+3+x+2)=(x+3)(3x+6)=
=3(x+3)(x+1)
i)(x+y)(x-y-x^2-y^2-2x+y)=(x+y)(-x-x^2-y^2)
j)(x+1)[x+1+2-(x+1)^2+x-5)=
=(x+1)(2x-2-x^2+2x-1)=(x+1)(4x-x^2-3)
k)(x-y)(x+y+x-y-3x+2y+x+3y)=(x-y)5y
l)(x-3y)(4+x+1-y+1+x-3y)=(x-3y)(2x-4y+6)